Describe in words a sequence of transformations that maps ∆ABC to ∆A'B'C'.
Transformation #1


Transformation #2


Write an ordered-pair rule for each transformation in the sequence.
Transformation #1


Transformation #2

Describe in words a sequence of transformations that maps ABC to ABC Transformation 1 Transformation 2 Write an orderedpair rule for each transformation in the class=

Respuesta :

First is a 90Âş rotation (counter-clockwise) with respect to the origin. Next is a horizontal transformation of +2 units. Transformation one is (x, y) -> (-y, x) Transformation two is (x, y) -> (x + 2, y)

Answer:  The required sequence of transformations is

Transformation 1 : a rotation by 90 degrees in the counterclockwise direction about the origin, (x, y) ⇒  (-y, x).

Transformation 2 : a translation by 2 units right and 3 units down, (x, y) ⇒ (x+2, y-3).

Step-by-step explanation:  We are given to describe in words a sequence of transformations that maps ∆ABC to ∆A'B'C'.

From the figure, we note that

the co-ordinates of the vertices of triangle ABC are A(0, 4), B(0, 0) and C(2, 3).

And, the co-ordinates of the vertices of triangle A'B'C' are A'(-2, -3), B'(2, -3) and C'(-1, -1).

We see that if triangle ABC is rotated 90 degrees in anticlockwise direction about the origin, then its co-ordinates changes according to the following rule :

(x, y)  ⇒  (-y, x).

That is

A(0, 4)  ⇒  (-4, 0),

B(0, 0)   ⇒ (0, 0),

C(2, 3)    ⇒ (-3, 2).

Now, if the vertices of the rotated triangle are translated  2 units right and 3 units down, then

(x, y)  ⇒  (x+2, y-3).

That is, the final co-ordinates after rotation and translation will be

(-4, 0)  ⇒  (-4+2, 0-3) = (-2, -3),

(0, 0)   ⇒ (0+2, 0-3) = (2, -3),

(-3, 2)   ⇒ (-3+2, 2-3) = (-1, -1).

We see that the final co-ordinates are the co-ordinates of the vertices of triangle A'B'C'.

Thus, the required sequence of transformations is

Transformation 1 : a rotation by 90 degrees in the counterclockwise direction about the origin, (x, y) ⇒  (-y, x).

Transformation 2 : a translation by 2 units right and 3 units down, (x, y) ⇒ (x+2, y-3).